Application of PVDF ultrafiltration membranes to treat and reuse textile wastewater. Issue 18 (14th April 2016) - Buscio, V.; Crespi, M.; Gutiérrez-Bouzán, C.
Abstract: In this work, the feasibility of polyvinylidene difluoride ultrafiltration membranes to treat textile wastewater was studied. The C.I. Disperse Orange 30 and C.I. Disperse Rubine 73 were selected as pollutant for the membrane filtration study. The results showed about 90 and 96% of COD decrease and dye removal, respectively. In addition, very low fouling was observed which demonstrated the feasibility of applying this type of membranes to treat textile wastewater. Finally, after the membrane treatment, 100% of the obtained permeate was reused. Fabrics dyed with the reused water were evaluated with respect to references carried out with softened tap water. No significant colour differences were observed between reference fabrics and the fabrics dyed with the permeate.